Consonant Clusters in Manggaraian Name Differentiate Gender: Perspective of Cultural Linguistics (e-Journal of Linguistics, 2025)
This article discusses Consonant Clusters (CC) in Manggaraian Name (MN). CC constitutes two or more different consonants is one syllable. In Theory of Cultural Linguistics, CC belongs to verbal symbols. They are based in cultural imagery of Manggaraian Language Speakers (MLS). The data were obtained from observation on MN consisting of Male Manggaraian Names (MMN) and Female Manggaraian Name (FMN).CC is homorganly formed from nasal-sonorants-continuants /m/, /n/, and /ng/ and stop consonant/b/, /p/, /d/, /t/, /g/, /k/, and affricate consonant /c/ and /j/forming eight CC: /mb/, /mp/, /nc/, /nd/, /nj/, /nt/, /ngg/, and /ngk/. They occur more in MMN than they do in FMN. They combine with different vowel frequency. They include /ngg/, /mb/, /nd/, /mp/, /ngk/, /nt/, /nc/, and/nj/ in MMN, but /nd/, /mb/, /ngg/, /nt/, /mp/, /ngk/, /nc/, and /nj/ in FMN respectively. CC differences in MN reflect cultural imagery difference of MLS on gender. MN has cultural consonant clusters
Keywords: Consonant Clusters; Cultural Imagery; Manggaraian Names; Verbal Symbol